Ibn Khaldūn’s Social Thought on Bedouin and Ḥaḍar - Moh. Pribadi (Al-Jami'ah: Journal of Islamic Studies, 2014)
Through the framework of modern sociological theory equipped with methods of historical and sociological interpretation of the text, this study attempted to explain Ibn Khaldūn’s social thought, especially the Bedouin and ḥaḍar, in ‘ilm al-‘umrān. Ibn Khaldūn’s idea on social importance was about the bedouin and ḥaḍar community along with their social solidarity. Both communities had their respective characteristics. Nomadic society which was identical to the bedouin community had a social structure and specificity as tendency in virtue, warm relationship, and uniformity, while ḥaḍar society had a structure and social peculiarities such as pluralist, pragmatic, and hedonists. In terms of lifestyle, bedouin society looked more dynamic than ḥaḍar. Bedouin way of life was characterized by moving from one place to another, and this made this community smart in formulating the vision, mission, programs, and targets to be achieved in life. Bedouin specificity was reflected in their lives’ readiness and supplies, one thing that was not visible in the community of ḥaḍar. Meanwhile, with their prosperity, ḥaḍar people were busy with urban activity and civil society development. Ibn Khaldūn had sought to understand human being and his existence individually or socially through ‘ilm al-‘umrān. His social methodology reflected his overall views through observation of social reality in a comprehensive manner. The author argued that Ibn Khaldūn’s social methodology that combined data and social facts with religion could be a reference and served as an example of a comprehensive approach. Ibn Khaldūn’s another important idea was on the development of community intelligence which included three stages: tamyīzī, tajrībī, and naẓārī.[Melalui kerangka teori sosiologi modern serta metode penafsiran teks secara historis-sosiologis, penelitian ini berusaha untuk menjelaskan pemikiran sosial Ibn Khaldun tentang masyarakat badui dan ḥaḍar. Ide Ibnu Khaldun tentang masyarakat dapat dilihat pada konsepnya mengenai dua masyarakat ini beserta solidaritas sosial mereka, dengan karakteristik masing-masing. Masyarakat nomaden yang identik dengan masyarakat badui memiliki struktur sosial dan spesifisitas dengan kecenderungan pada kebajikan, ramah, dan keseragaman; sementara masyarakat ḥaḍar memiliki struktur dan kekhasan sosial seperti pluralis, pragmatis, dan hedonis. Dalam hal gaya hidup, masyarakat badui tampak lebih dinamis daripada ḥaḍar. Cara hidup masyarakat badui ditandai dengan terus berpindah dari satu tempat ke tempat lain, dan ini membuat komunitas ini cerdas dalam merumuskan visi, misi, program, dan sasaran yang ingin dicapai dalam hidup. Spesifisitas badui tercermin dalam kesiap-siagaan mereka, satu hal yang tidak terlihat dalam komunitas ḥaḍar. Sementara itu, dengan kemakmuranya, orang ḥaḍar sibuk dengan aktivitas perkotaan dan pembangunan masyarakat sipil. Ibn Khaldun telah berusaha untuk memahami manusia dan keberadaannya secara individu ataupun sosial melalui ‘ilm al-‘umrān. Metodologi sosialnya mencerminkan pandangannya secara keseluruhan melalui pengamatan realitas sosial secara komprehensif. Penulis berpendapat bahwa metodologi sosial Ibn Khaldun yang menggabungkan data dan fakta sosial dengan agama bisa menjadi referensi dan contoh pendekatan yang komprehensif. Ide penting Ibnu Khaldun lainnya adalah tentang perkembangan kecerdasan masyarakat yang meliputi tiga tahap: tamyīzī, tajrībī, dan naẓārī.]